2017
DOI: 10.11138/gchir/2017.38.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Primitive squamous cell carcinoma of the breast (SCCB): case report of an uncommon variant of metaplastic carcinoma

Abstract: SUMMARY: Primitive squamous cell carcinoma of the breast (SCCB): case report of an uncommon variant of metaplastic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…SATO’s ( 24 ) research have shown that patients with BSqCC had a median overall disease-free survival of only 20 months; and the 5-year disease-free survival rate was 26%; the 5-year median survival was 37 months; and the 5-year overall survival rate was only 40%. Another study of 11 patients with primary squamous cell carcinoma of the breast who were treated and followed up for 30 years reported a 5-year survival rate of 67% ( 25 ). Our study showed that the median survival time was 44 months; the 3-year survival rate was 62.9%; the 5-year survival rate was 54.4%; and the 10-year survival rate was 41.4%.…”
Section: Discussionmentioning
confidence: 99%
“…SATO’s ( 24 ) research have shown that patients with BSqCC had a median overall disease-free survival of only 20 months; and the 5-year disease-free survival rate was 26%; the 5-year median survival was 37 months; and the 5-year overall survival rate was only 40%. Another study of 11 patients with primary squamous cell carcinoma of the breast who were treated and followed up for 30 years reported a 5-year survival rate of 67% ( 25 ). Our study showed that the median survival time was 44 months; the 3-year survival rate was 62.9%; the 5-year survival rate was 54.4%; and the 10-year survival rate was 41.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological diagnostic criteria of MSCCB include: a) more than 90% of the tumor cells are squamous, and other components could include spindle cells, ductal cells, osteocytes, chondrocytes, and striated muscle cells; [6][7][8] b) the origin is independent of primary SCC in a distant site from the skin; and c) is possible after excluding the nipple or the overlying skin primary lesion. 5,8,12,13 When SCC is found in the breast, the origin of the lesion should be sought due to the rarity of MSCCB. Extramammary SCCs have a tendency to metastasize to the breast; the most common primary sites are lung, esophagus, cervix, and urinary bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors, however, hypothesize that it may originate from myoepithelial cells [ 7 , 8 ]. In our experience, we observed another case of squamous carcinoma in an elderly woman, in whom the clinical onset was associated with an inflammatory cyst [ 9 ].…”
Section: Discussionmentioning
confidence: 99%